High-strength repairing mortar and preparation method thereof
By using equal proportions of components A and B to form high-strength repair mud, and using modified graphite powder and other components, the existing repair mud is solved, and the repair effect of high-strength and rapid curing is achieved, and it is suitable for a wide range of repair applications.
Patent Information
- Application Number
- CN202411879008.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-14
AI Technical Summary
Existing repair muds have shortcomings in terms of mechanical strength and applicability, which are difficult to meet the broader repair needs, especially in engineering pipeline restoration and construction applications.
By using equal proportions of component A and component B to form high-strength repair mud, component A includes epoxy resin, talc powder, barium sulfate, modified graphite powder, etc. Component B includes curing agent, talc powder, barium sulfate, etc. The modified graphite powder is prepared by surface oxidation and high-temperature carbonization treatment to ensure that the mud has high mechanical strength after curing.
It realizes the high mechanical strength and rapid curing characteristics after hardening of the cement. It is suitable for the combination of a variety of hard materials. It has good overall applicability and can be repaired quickly and conveniently.
Smart Images

Figure BDA0005197699780000081 
Figure BDA0005197699780000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy resin mortar preparation, and in particular to high-strength repair mortar and a preparation method thereof. Background Art
[0002] Glue is a mud-like plastic solid with strong adhesive properties. This type of plastic solid is sticky and has a certain strength after solidification. It can be used as a repair material for daily pipelines or construction. Currently, the most common repair glues are two-component products of epoxy or unsaturated polyester. They generally have high hardness and good reinforcement effect. They can be used for thickening wall structures and repairing various types of water leaks.
[0003] Different repair environments generally have different requirements for the repair effect and performance of the mastic. However, for mastic materials, higher mechanical strength can be applied to a wider range of scenarios, especially for engineering pipeline repairs or construction applications. Therefore, improving the strength of the mastic by adjusting its composition is an important direction for the research and development of mastic at this stage. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a high-strength repair mortar and a preparation method thereof, which can effectively improve the mechanical strength of the mortar after hardening while ensuring good adhesion of the mortar, thereby comprehensively improving the repair effect of the mortar.
[0005] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:
[0006] A high-strength repair mortar, which is composed of component A and component B in equal proportions; component A is composed of the following materials in parts by weight: 18-22 parts of epoxy resin, 45-50 parts of talc, 14-16 parts of barium sulfate, 2-4 parts of modified graphite powder, 1-2 parts of calcium stearate, 0.2-0.4 parts of dodecylphenol, and 2-4 parts of graded particle size quartz powder; component B is composed of the following materials in parts by weight: 18-22 parts of curing agent, 45-50 parts of talc, 35-40 parts of barium sulfate, and 1-3 parts of titanium dioxide; the modified graphite powder is obtained by surface-oxidizing graphite powder, mixing it with asphalt, high-temperature treating it, and then crushing it.
[0007] Preferably, the method for preparing the modified graphite powder comprises the following steps:
[0008] S1. Disperse the graphite powder in 1 mol / L NaOH solution, then drop 30% hydrogen peroxide solution, stir magnetically at 35±2°C for 12-16h, centrifuge to remove the precipitate, rinse with water and dry to obtain surface oxidized graphite powder;
[0009] S2. Add 4%-6% asphalt to the total mass of the surface oxidized graphite powder, mix and stir evenly, place at 400-450°C for carbonization treatment, then heat to 800-850°C for further high temperature treatment, and then crush through a 120-mesh sieve to obtain modified graphite powder.
[0010] Preferably, in step S1, the mass ratio of the NaOH solution to the hydrogen peroxide solution is 10:1.
[0011] Preferably, the carbonization treatment time in step S2 is 3 hours, and the high temperature treatment time is 1 hour.
[0012] Preferably, the graded particle size quartz powder is obtained by mixing 400 mesh quartz powder, 600 mesh quartz powder and 800 mesh quartz powder in a mass ratio of 6:3:2.
[0013] Preferably, the curing agent is a polythiol curing agent.
[0014] The preparation method of high-strength repair mortar comprises the following steps:
[0015] (1) placing an epoxy resin in a reaction kettle, replacing the oxygen in the reaction kettle with nitrogen, then adding talcum powder, barium sulfate, modified graphite powder, calcium stearate, dodecylphenol, and graded quartz powder, stirring and mixing evenly, and then taking out component A;
[0016] (2) adding the curing agent to talcum powder, barium sulfate and titanium dioxide, stirring and mixing evenly, and then taking out to obtain component B;
[0017] (3) When using, knead equal amounts of component A and component B for 2-3 minutes to obtain a high-strength repair mortar that can be used immediately after preparation.
[0018] Preferably, the stirring and mixing speed in step (1) is 200-400 r / min, and the stirring time is 30-40 min.
[0019] Preferably, the stirring and mixing speed in step (2) is 200-400 r / min, and the stirring time is 20-30 min.
[0020] The present invention provides a high-strength repair mortar and a preparation method thereof, which has the following advantages over the prior art:
[0021] The present invention adopts the form of A and B components to prepare the glue, which is prepared on the spot when used, and the amount of the glue can be controlled according to demand. The glue has a fast hardening speed and can quickly repair the corresponding parts. The hardened glue has high mechanical strength and can combine a variety of hard materials. It has good overall applicability and hardens quickly, achieving the purpose of fast and convenient repair. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The epoxy resin used below is epoxy resin E44, purchased from Wuxi Qianguang Chemical Raw Materials Co., Ltd.; the curing agent used is 3800 polythiol curing agent, purchased from Shanghai Kaiyin Chemical Co., Ltd.
[0024] Embodiment 1:
[0025] Preparation of repair glue:
[0026] (1) Preparation of modified graphite powder:
[0027] Graphite powder was evenly dispersed in 1 mol / L NaOH solution, 30% hydrogen peroxide solution (the mass ratio of NaOH solution to hydrogen peroxide solution was 10:1), magnetically stirred at 35±2°C for 12h, then centrifuged to remove the precipitate, rinsed with water and dried at 45°C to obtain surface oxidized graphite powder;
[0028] Add 4% asphalt to the surface oxidized graphite powder, mix and stir evenly, place at 400°C for carbonization treatment for 3 hours, then heat to 800°C for 1 hour, and then grind through a 120-mesh sieve to obtain modified graphite powder;
[0029] (2) Prepare the materials according to the following weight parts:
[0030] Component A: 18 parts of epoxy resin, 45 parts of talc, 14 parts of barium sulfate, 2 parts of modified graphite powder, 1 part of calcium stearate, 0.2 parts of dodecylphenol, 2 parts of graded particle size quartz powder (400 mesh: 600 mesh: 800 mesh = 6:3:2);
[0031] Component B: 18 parts of curing agent, 45 parts of talc, 35 parts of barium sulfate, 1 part of titanium dioxide;
[0032] (3) placing epoxy resin in a reaction kettle, replacing oxygen in the reaction kettle with nitrogen, then adding talcum powder, barium sulfate, modified graphite powder, calcium stearate, dodecylphenol, and graded quartz powder, stirring at 200 r / min for 40 min, and then taking out component A;
[0033] (4) Add the curing agent to talcum powder, barium sulfate and titanium dioxide, stir at 200 r / min for 30 min, and then take out component B.
[0034] Embodiment 2:
[0035] Preparation of repair glue:
[0036] (1) Preparation of modified graphite powder:
[0037] The graphite powder was evenly dispersed in a 1 mol / L NaOH solution, and then magnetically stirred at 35±2°C for 16 hours. The precipitate was then centrifuged and washed with water and dried at 45°C to obtain surface oxidized graphite powder.
[0038] Add 6% asphalt to the surface oxidized graphite powder, mix and stir evenly, place at 450°C for carbonization treatment for 3 hours, then heat to 850°C for 1 hour, and then grind through a 120-mesh sieve to obtain modified graphite powder;
[0039] (2) Prepare the materials according to the following weight parts:
[0040] Component A: 22 parts of epoxy resin, 50 parts of talc, 16 parts of barium sulfate, 4 parts of modified graphite powder, 2 parts of calcium stearate, 0.4 parts of dodecylphenol, 4 parts of graded particle size quartz powder (400 mesh: 600 mesh: 800 mesh = 6:3:2);
[0041] Component B: 22 parts of curing agent, 50 parts of talc, 40 parts of barium sulfate, 3 parts of titanium dioxide;
[0042] (3) placing epoxy resin in a reaction kettle, replacing oxygen in the reaction kettle with nitrogen, then adding talcum powder, barium sulfate, modified graphite powder, calcium stearate, dodecylphenol, and graded quartz powder, stirring at 400 r / min for 30 min, and then taking out component A;
[0043] (4) Add the curing agent to talcum powder, barium sulfate and titanium dioxide, stir at 400 r / min for 20 min, and then take out component B.
[0044] Comparative Example 1:
[0045] Preparation of repair glue:
[0046] (1) Preparation of modified graphite powder:
[0047] Add 4% asphalt to the total weight of the graphite powder, mix and stir evenly, place at 400°C for carbonization treatment for 3 hours, then heat to 800°C for 1 hour, and then grind through a 120-mesh sieve to obtain modified graphite powder;
[0048] (2) Prepare the materials according to the following weight parts:
[0049] Component A: 18 parts of epoxy resin, 45 parts of talc, 14 parts of barium sulfate, 2 parts of modified graphite powder, 1 part of calcium stearate, 0.2 parts of dodecylphenol, 2 parts of graded particle size quartz powder (400 mesh: 600 mesh: 800 mesh = 6:3:2);
[0050] Component B: 18 parts of curing agent, 45 parts of talc, 35 parts of barium sulfate, 1 part of titanium dioxide;
[0051] (3) placing epoxy resin in a reaction kettle, replacing oxygen in the reaction kettle with nitrogen, then adding talcum powder, barium sulfate, modified graphite powder, calcium stearate, dodecylphenol, and graded quartz powder, stirring at 200 r / min for 40 min, and then taking out component A;
[0052] (4) Add the curing agent to talcum powder, barium sulfate and titanium dioxide, stir at 200 r / min for 30 min, and then take out component B.
[0053] Comparative Example 2:
[0054] Preparation of repair glue:
[0055] (1) Prepare the materials according to the following weight parts:
[0056] Component A: 18 parts of epoxy resin, 45 parts of talc, 14 parts of barium sulfate, 2 parts of graphite powder, 1 part of calcium stearate, 0.2 parts of dodecylphenol, 2 parts of graded particle size quartz powder (400 mesh: 600 mesh: 800 mesh = 6:3:2);
[0057] Component B: 18 parts of curing agent, 45 parts of talc, 35 parts of barium sulfate, 1 part of titanium dioxide;
[0058] (2) placing epoxy resin in a reaction kettle, replacing oxygen in the reaction kettle with nitrogen, then adding talcum powder, barium sulfate, graphite powder, calcium stearate, dodecylphenol, and graded quartz powder, stirring at 200 r / min for 40 min, and then taking out component A;
[0059] (3) Add the curing agent to talcum powder, barium sulfate and titanium dioxide, stir at 200 r / min for 30 min, and then take out component B.
[0060] Comparative Example 3:
[0061] Preparation of repair glue:
[0062] (1) Preparation of modified graphite powder:
[0063] Graphite powder was evenly dispersed in 1 mol / L NaOH solution, 30% hydrogen peroxide solution (the mass ratio of NaOH solution to hydrogen peroxide solution was 10:1), magnetically stirred at 35±2°C for 12h, then centrifuged to remove the precipitate, rinsed with water and dried at 45°C to obtain surface oxidized graphite powder;
[0064] Add 4% asphalt to the surface oxidized graphite powder, mix and stir evenly, place at 400°C for carbonization treatment for 3 hours, then heat to 800°C for 1 hour, and then grind through a 120-mesh sieve to obtain modified graphite powder;
[0065] (2) Prepare the materials according to the following weight parts:
[0066] Component A: 18 parts of epoxy resin, 45 parts of talc, 14 parts of barium sulfate, 2 parts of modified graphite powder, 1 part of calcium stearate, 0.2 parts of dodecylphenol, 2 parts of quartz powder (400 mesh);
[0067] Component B: 18 parts of curing agent, 45 parts of talc, 35 parts of barium sulfate, 1 part of titanium dioxide;
[0068] (3) placing epoxy resin in a reaction kettle, replacing oxygen in the reaction kettle with nitrogen, then adding talcum powder, barium sulfate, modified graphite powder, calcium stearate, dodecylphenol, and quartz powder, stirring at 200 r / min for 40 min, and then taking out component A;
[0069] (4) Add the curing agent to talcum powder, barium sulfate and titanium dioxide, stir at 200 r / min for 30 min, and then take out component B.
[0070] Comparative Example 4:
[0071] Preparation of repair glue:
[0072] (1) Preparation of modified graphite powder:
[0073] Graphite powder was evenly dispersed in 1 mol / L NaOH solution, 30% hydrogen peroxide solution (the mass ratio of NaOH solution to hydrogen peroxide solution was 10:1), magnetically stirred at 35±2°C for 12h, then centrifuged to remove the precipitate, rinsed with water and dried at 45°C to obtain surface oxidized graphite powder;
[0074] Add 4% asphalt to the surface oxidized graphite powder, mix and stir evenly, place at 400°C for carbonization treatment for 3 hours, then heat to 800°C for 1 hour, and then grind through a 120-mesh sieve to obtain modified graphite powder;
[0075] (2) Prepare the materials according to the following weight parts:
[0076] Component A: 18 parts of epoxy resin, 45 parts of talc, 14 parts of barium sulfate, 2 parts of modified graphite powder, 1 part of calcium stearate, 0.2 parts of dodecylphenol, 2 parts of graded particle size quartz powder (400 mesh: 600 mesh: 800 mesh = 6:3:2);
[0077] Component B: 18 parts of curing agent, 45 parts of talc, 35 parts of barium sulfate, 1 part of titanium dioxide;
[0078] (3) placing epoxy resin in a reaction kettle, adding talcum powder, barium sulfate, modified graphite powder, calcium stearate, dodecylphenol, and graded quartz powder, stirring at 200 r / min for 40 min, and then taking out component A;
[0079] (4) Add the curing agent to talcum powder, barium sulfate and titanium dioxide, stir at 200 r / min for 30 min, and then take out component B.
[0080] Detection:
[0081] The performance tests were performed on the mortars prepared in the above Examples 1-2 and Comparative Examples 1-4:
[0082] 1. Take the components A and B of each group of cement and knead them for 2 minutes, then record the initial curing time (starting from the time of kneading) and the hardness after 24 hours (Shore durometer test). The specific results are shown in Table 1 below:
[0083] Table 1
[0084]
[0085]
[0086] The cement prepared in the above-mentioned embodiments 1-2 has a higher hardness.
[0087] 2. Take the components A and B of each group of glue and knead them for 2 minutes, then bond two stainless steel plates. After curing for 24 hours, test the shear strength. The specific results are shown in the following table:
[0088] Table 2
[0089]
[0090] It can be seen from the above table that the cement prepared in Example 1-2 has a higher shear strength when used.
[0091] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength repair mortar, characterized in that: The high-strength repair mortar is composed of component A and component B in equal proportions; The component A is composed of the following materials in parts by weight: 18-22 parts of epoxy resin, 45-50 parts of talc, 14-16 parts of barium sulfate, 2-4 parts of modified graphite powder, 1-2 parts of calcium stearate, 0.2-0.4 parts of dodecylphenol, and 2-4 parts of graded particle size quartz powder; The component B is composed of the following materials in parts by weight: 18-22 parts of curing agent, 45-50 parts of talc, 35-40 parts of barium sulfate, and 1-3 parts of titanium dioxide; The modified graphite powder is obtained by oxidizing the surface of graphite powder, mixing it with asphalt, treating it at high temperature, and then crushing it.
2. A high-strength repair mortar according to claim 1, characterized in that: The preparation method of the modified graphite powder comprises the following steps: S1. Disperse the graphite powder in 1 mol / L NaOH solution, then drop 30% hydrogen peroxide solution, stir magnetically at 35±2°C for 12-16h, centrifuge to remove the precipitate, rinse with water and dry to obtain surface oxidized graphite powder; S2. Add 4%-6% asphalt to the total mass of the surface oxidized graphite powder, mix and stir evenly, place at 400-450°C for carbonization treatment, then heat to 800-850°C for further high temperature treatment, and then crush through a 120-mesh sieve to obtain modified graphite powder.
3. The high-strength repair mortar according to claim 2, characterized in that: In step S1, the mass ratio of the NaOH solution to the hydrogen peroxide solution is 10:
1.
4. The high-strength repair mortar according to claim 2, characterized in that: The carbonization treatment time in step S2 is 3 hours, and the high temperature treatment time is 1 hour.
5. The high-strength repair mortar according to claim 1, characterized in that: The graded particle size quartz powder is obtained by mixing 400 mesh quartz powder, 600 mesh quartz powder and 800 mesh quartz powder in a mass ratio of 6:3:
2.
6. The high-strength repair mortar according to claim 1, characterized in that: The curing agent is a polythiol curing agent.
7. A method for preparing the high-strength repairing mortar according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) placing an epoxy resin in a reaction kettle, replacing the oxygen in the reaction kettle with nitrogen, then adding talcum powder, barium sulfate, modified graphite powder, calcium stearate, dodecylphenol, and graded quartz powder, stirring and mixing evenly, and then taking out component A; (2) adding the curing agent to talcum powder, barium sulfate and titanium dioxide, stirring and mixing evenly, and then taking out to obtain component B; (3) When using, knead equal amounts of component A and component B for 2-3 minutes to obtain a high-strength repair mortar that can be used immediately after preparation.
8. The preparation method according to claim 7, characterized in that: The stirring and mixing in step (1) is performed at a speed of 200-400 r / min, and the stirring time is 30-40 min.
9. The preparation method according to claim 7, characterized in that: The stirring and mixing in step (2) is performed at a speed of 200-400 r / min, and the stirring time is 20-30 min.